Silver alert : a novel - Smith, Lee, 1944- (Algonquin Books of Chapel Hill, 2023)
Herb's charmed life with his dear wife, Susan, in their Key West house is coming undone. Susan, in her seventies, now needs constant care, and Herb is in denial about his own ailing health. The one bright spot is the arrival of an endlessly optimistic manicurist calling herself Renee. She sings to Susan during manicures, gets her to paint, and brings her a much-needed sense of contentment. But then Herb and Susan's adult children arrive to stage an intervention on their stubborn, independent father, and as a consequence, Renee's gig with Susan--and her grand plans for her own life--start to unravel as well. Herb isn't ready to let go of all that he has ever had, and it turns out that Renee is not the happy, uncomplicated girl she pretends to be. She is not even Renee; she is really Dee Dee, and she, too, has reasons of her own to hit the road. So, when Herb suggests one last joy ride in his Porsche with Dee Dee riding shotgun, they light out for parts north, setting off a Silver Alert. As the unlikely friendship between Herb and Dee Dee deepens, we see how one life opens up as another is closing down. The time Dee Dee has spent--with Susan, in Key West, in the Porsche with elderly Herb--reveals to her how much more truly lies ahead.